Jews and Ukrainians : a millennium of co-existence - Magocsi, Paul R. 1945- (University of Toronto Press, 2016)
"This volume surveys various past and present aspects of Jews and ethnic Ukrainians on the territory of Ukraine and in the diaspora."--